Role of Scleral Contact Lenses in Management of Coexisting Keratoconus and Stevens–Johnson Syndrome. Issue 10 (October 2017) - Rathi, Varsha M.; Taneja, Mukesh; Dumpati, Srikanth; Mandathara, Preeji S.; Sangwan, Virender S.
Abstract : Purpose: To report the rare coexistence of keratoconus and Stevens–Johnson syndrome (SJS) managed with scleral contact lenses (ScCLs). Methods: This is a retrospective case series. Five patients (9 eyes) who had coexisting SJS and corneal ectasia were identified from the database during the 2-year period. Diagnosis of SJS was based on a positive history of drug reactions, signs of ocular surface disease, and the presence of keratinization of lid margins. Keratoconus was diagnosed by slit-lamp biomicroscopy. Results: Five eyes of 3 patients had coexisting SJS and keratoconus and were dispensed with ScCLs (PROSE, prosthetic replacement of the ocular surface ecosystem; Boston Foundation for Sight, Needham Heights, MA). All these patients had photophobia. Visual acuity improved in all these patients with ScCL wear. Two patients (4 eyes) were excluded from this study because they had SJS with generalized corneal thinning from limbus to limbus, corneal opacification, and pannus. One patient developed deep vessels in the cornea on prolonged ScCL wear. Reduction in the ScCL wear schedule and change of material with a higher Dk resulted in regression of vascularization. Case 3 developed conjunctival congestion and was uncomfortable wearing ScCLs, although visual acuity was 20/40. He discontinued using ScCL wear. Conclusions: Keratoconus, a noninflammatory condition of the cornea coexisted with inflammatory SJS. Managing such patients with ScCLs may improve vision and comfort.